RETAIL GROWTH AND DIGITAL TRANSFORMATION FRAMEWORK: A STRATEGIC APPROACH FOR BUSINESS SUSTAINABILITY - Evy Oktaviani Fauzi (Journal Of Resource Management, Economics And Business, 2026)
Purpose: The purpose of this study is to develop a comprehensive Retail Growth and Digital Transformation Framework that integrates multiple established business models to guide retail businesses in navigating growth, digital transformation, and customer satisfaction Research Methodology: This study utilizes a qualitative approach, synthesizing six business models: McKinsey’s 3 Horizons, BCG’s Growth Share Matrix, Bain & Company’s NPS, Deloitte’s Digital Maturity Model, Accenture’s Value Chain Analysis, and PwC’s SARAH Model. Tools and software used include Microsoft Excel, Tableau, and NVivo for data analysis, visualization, and qualitative synthesis. Results: The synthesis of these models into a unified framework provides a strategic tool for balancing short-term operational efficiency with long-term innovation, improving customer loyalty, and ensuring successful digital transformation. Limitations: This study assumes that retail businesses have varying levels of digital maturity. The framework’s applicability across all retail sectors and geographical regions requires further empirical validation. Contribution: This framework is valuable for retail leaders, strategic planners, and business consultants in industries such as retail management, digital transformation, and customer experience. It can aid in guiding retail businesses through complex challenges and technological advancements.